PENINGKATAN KEPUASAN KERJA GURU DENGAN CARA PENGUATAN KEPEMIMPINAN TRANSFORMASIONAL DAN BUDAYA ORGANISASI - Siti Julaeha; M Entang; Herfina . (JURNAL MANAJEMEN PENDIDIKAN, 2020)
IMPROVING TEACHER JOB SATISFACTION BY STRENGTHENING TRANSFORMATIONAL LEADERSHIP AND ORGANIZATIONAL CULTUREThis study is intended to empirically determining teacher job satisfaction by strengthening transformational leadership and organizational culture of honorary teachers of private vocational schools at Cibungbulang District. The number of research sample was 158 teachers taken using proportional random sampling techniques. The utilizing method was the correlational method. Hypothesis testing was carried out using parametric statistical analysis in the form of simple and multiple linear regression analysis, simple and multiple correlation analysis with significance levels α = 0.01 and α = 0.05. This research resulted in four conclusions. Firstly, there was a positive and significant relationship between transformational leadership and teacher job satisfaction where the correlation coefficient ry1 = 0.588, the coefficient of determination Ry12 = 0.3461.  Secondly, there was a positive and significant relationship between organizational culture and teacher job satisfaction where the correlation coefficient ry2 = 0.626, the coefficient of determination Ry22 = 0.3914. Thirdly, there was a positive and significant relationship between both transformational leadership and organizational culture with teacher job satisfaction where the correlation coefficient ry.12 = 0.71 and the coefficient of determination Ry.122 = 0.504. Fourthly, the job satisfaction could be improved by strengthening transformational leadership and organizational culture, both separately or altogether. It can be concluded that teacher job satisfaction can be improved by strengthening transformational leadership and organizational culture.